Evaporation lifetime and boiling curve on hemispherical stainless steel (304) surface - Illias, S; Rosman, N A; Abdullah, N S; Shaiful, A I M; Omar, M N B; Ismail, K A; Ani, Mohd Hanafi (Institute of Physics Publishing, 2019)
The purpose of this research is to study and investigate the evaporation lifetime and boiling curve on a hemispherical heated surface. The selected material was stainless steel (304). A nearly perfect and smooth hemispherical surface was developed by using EDM die sinker. For the test liquid, distilled water was used during the experimental work. The average droplet temperature was 31.36 °C corresponding to liquid subcooling ∆Tsub = 68.64K. Based on the theoretical calculation, the diameter of the water droplet was approximately 5.00 mm. Meanwhile, the impact height was approximately 65.0 mm corresponding to the theoretical impact velocity of 1.129 m/s. The material was heated using a digital hot plate which was able to give an accurate reading and stable temperature fluctuation during the heating process. The temperature ranged from a low temperature of Tw = 100 °C to a high temperature of Tw = 300 °C. As a result, the boiling curve showed a similar pattern of other experimental work that consists of two (2) important points which are the Critical Heat Flux (CHF) and Leidenfrost temperature.